How does a newly born mouse get to the nipple? odor substrates eliciting first nipple grasping and sucking responses. Issue 8 (4th October 2012) - Al Aïn, Syrina; Belin, Laurine; Schaal, Benoist; Patris, Bruno
Abstract It is a mammalian female strategy to emit odor cues and signals that direct their inexperienced newborns to the nipple, and optimize their initial sucking success and, hence, viability. Here, natural odorous substrates that contribute to nipple grasping were investigated in mice, a species that has not been much scrutinized on this topic. The response of pups toward the nipples of lactating females (LF) versus nonlactating females (NLF) were first assessed right after watched birth, before and after the first suckling experience, and at 1 day old, after more extended suckling experience. It appeared that only nipples of LF induced grasping at these early ages, leading to take NLF as the baseline setting to present various odor substrates sampled from LF, viz. amniotic fluid, murine milk, LF saliva, pup saliva, LF urine, and an odorless control stimulus (water). Results indicate that: (1) only amniotic fluid and fresh milk induced nipple grasping before the first suckling experience; (2) LF saliva started inducing grasping after the first suckling experience; (3) pup saliva released grasping after 24–36 hr of suckling experience; finally (4) neither LF urine, nor water induced any nipple grasping. In conclusion, the activity of amniotic fluid and murine milk on neonatal pup behavior before any postnatal suckling experience suggests that either prenatal learning and/or predisposed olfactory mechanisms do operate, while the behavioral activation due to maternal and infantile salivas clearly depends on postnatal exposure. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 888–901, 2013.